2013
DOI: 10.1017/jfm.2013.18
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of droplet breakup in a T-junction

Abstract: The breakup of droplets due to creeping motion in a confined microchannel geometry is studied using three-dimensional numerical simulations. Analogously to unconfined droplets, there exist two distinct breakup phases: (i) a quasi-steady droplet deformation driven by the externally applied flow; and (ii) a surface-tension-driven three-dimensional rapid pinching that is independent of the externally applied flow. In the first phase, the droplet relaxes back to its original shape if the externally applied flow st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(89 citation statements)
references
References 19 publications
8
79
2
Order By: Relevance
“…However, as suggested by two-dimensional numerical simulations [22] and shown by this work, they are able to describe the flow of biphasic flows with reasonable accuracy in many situations. We believe that this kind of models can be of valuable use in the description of droplet microfluidics when confinement is important.…”
Section: Discussionmentioning
confidence: 65%
“…However, as suggested by two-dimensional numerical simulations [22] and shown by this work, they are able to describe the flow of biphasic flows with reasonable accuracy in many situations. We believe that this kind of models can be of valuable use in the description of droplet microfluidics when confinement is important.…”
Section: Discussionmentioning
confidence: 65%
“…Numerical simulations which provide a complete description of the flow field can shed light on the present problem. It has been shown that numerical approximations of the Navier-Stokes equations can represent flow physics in many microfluidics applications, such as droplets/bubbles migration and the breakup of droplets at T-junctions [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the effect of different gas and liquid distributors to find the controlled generation of the bubble and droplet formation of different flow regimes was investigated. Hoang et al (2013) investigated the droplet breakup dynamic with creeping motion through the T-shape microchannels using the VOF simulation method in OpenFOAM. Numerical validations of microfluidic flow simulation were examined.…”
Section: Introductionmentioning
confidence: 99%